2003
DOI: 10.1080/1606635031000062074
|View full text |Cite
|
Sign up to set email alerts
|

Gambling as emotion management: developing a grounded theory of problem gambling

Abstract: The numbers of individuals developing problems with gambling is on the increase. This study explored the nature of problem gambling through an analysis of the reported experiences of problem gamblers. A grounded theory approach involving the analysis of material from 14 male treatment seeking gamblers resulted in the identification of three main categories. These were emotion, control and costs of gambling. Central to the experience of all participants was the emotional nature of gambling, gambling being used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 27 publications
(38 reference statements)
2
26
0
1
Order By: Relevance
“…Gambling as a cognitive escape is central to many explanations of problem gambling (Blaszczynski and Nower 2002;Dickerson and Baron 2000;Lightsey and Hulsey 2002;Ricketts and Macaskill 2003;Rockloff and Dyer 2006;Wood and Griffiths 2007). Further, Surgey (2000) has discussed the "constructed environment" of EGM venues which provided a timeless refuge for women with gambling problems (p. 54), and Ladouceur et al (2005) found that probable pathological gamblers preferred to gamble in isolated areas of venues.…”
Section: Discussionmentioning
confidence: 95%
“…Gambling as a cognitive escape is central to many explanations of problem gambling (Blaszczynski and Nower 2002;Dickerson and Baron 2000;Lightsey and Hulsey 2002;Ricketts and Macaskill 2003;Rockloff and Dyer 2006;Wood and Griffiths 2007). Further, Surgey (2000) has discussed the "constructed environment" of EGM venues which provided a timeless refuge for women with gambling problems (p. 54), and Ladouceur et al (2005) found that probable pathological gamblers preferred to gamble in isolated areas of venues.…”
Section: Discussionmentioning
confidence: 95%
“…Money and internal stimuli such as cravings, positive memories of gambling, emotional conflict or negative emotional states (Wood and Griffiths 2007), financial problems, access to funds and lack of structured time (Ricketts and Macaskill 2003) also initiated gambling. In an Australian study of 13 problem gamblers, gambling was maintained by positive cognitions about winning, negative cognitions and affects associated with poor social support and relationship issues especially when a local pub offered a social space to retreat from responsibilities and home stressors (Thomas et al 2009).…”
Section: Qualitative Studies and Relapsementioning
confidence: 99%
“…This review has demonstrated relapse is associated with the duration of gambling, disinhibition, disadvantageous decision-making (Goudriaan et al 2008), urges, erroneous cognitions (Oei and Gordon 2008;Hodgins and el-Guebaly 2004), financial problems, access to funds, unstructured time (Ricketts and Macaskill 2003), money, internal stimuli (Wood and Griffiths 2007) and alcohol consumption (Hodgins and elGuebaly 2010). A limited ability to tolerate the discomfort of abstinence also leads to relapse (Daughters et al 2005).…”
Section: Qualitative Studies and Relapsementioning
confidence: 99%
“…A previous study Ricketts & Macaskill (2003) delineated a theory of problem gambling based on the experiences of treatment seeking male gamblers and allowed predictions to be made regarding the processes that differentiate between normal and problem gamblers. These predictions are the focus of the present study, which also utilised a grounded theory approach, but with a sample of male high frequency normal gamblers.…”
Section: Introductionmentioning
confidence: 99%
“…Ricketts and Macaskill (2003) addressed the nature of problem gambling through an analysis of the reported experiences of self-defined problem gamblers who were seeking treatment. The resulting grounded theory identified three main categories as emotion, control and the costs of gambling.…”
Section: Introductionmentioning
confidence: 99%